Policy Integration and Urban Growth: Skill India Mission’s Impact on Employment and Economic Activity in Bengaluru - Mangala T. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The Skill India Mission, launched by the Government of India in 2015, aims to transform the Indian workforce by equipping individuals with the skills necessary to meet the demands of the modern economy. With a focus on vocational training and industry-relevant skills, the mission seeks to bridge the gap between education and employment, thereby addressing the challenges of unemployment and underemployment in the country. Bengaluru, known as the Silicon Valley of India, presents a unique context for the implementation of this mission due to its dynamic and diverse economy. The rapid pace of technological advancement and the constant evolution of industry demands require a workforce that is not only highly skilled but also adaptable. Despite the efforts under the Skill India Mission, there are concerns about the effectiveness of the training programs in meeting these demands, particularly in a city like Bengaluru where the need for specialized skills is paramount.